2022
DOI: 10.1038/s41537-022-00224-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep rTMS of the insula and prefrontal cortex in smokers with schizophrenia: Proof-of-concept study

Abstract: Patients with schizophrenia have a high prevalence of cigarette smoking and respond poorly to conventional treatments, highlighting the need for new therapies. We conducted a mechanistic, proof-of-concept study using bilateral deep repetitive transcranial magnetic stimulation (dTMS) of insular and prefrontal cortices at high frequency, using the specialized H4 coil. Feasibility of dTMS was tested for disruption of tobacco self-administration, insula target engagement, and insula circuit modulation, all of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
1
15
0
2
Order By: Relevance
“…Another mechanistic, proof-of-concept study with the H4 coil revealed that participants assigned to active TMS were slower to initiate smoking their first cigarette than the sham group, an observation consistent with smoking disruption [39]. The neuroimaging data collected in this experiment showed an overall decrease in insula activity and changes in the resting-state connectivity between the insula and the default mode network (DMN) following active TMS.…”
Section: Extant Literature Of Tms For Substance Use Disorders Smoking...supporting
confidence: 63%
See 1 more Smart Citation
“…Another mechanistic, proof-of-concept study with the H4 coil revealed that participants assigned to active TMS were slower to initiate smoking their first cigarette than the sham group, an observation consistent with smoking disruption [39]. The neuroimaging data collected in this experiment showed an overall decrease in insula activity and changes in the resting-state connectivity between the insula and the default mode network (DMN) following active TMS.…”
Section: Extant Literature Of Tms For Substance Use Disorders Smoking...supporting
confidence: 63%
“…This multisite clinical trial was the result of several decades of work in both preclinical research laboratories and small clinical trials using a variety of TMS coils [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In 2020, the United States Food and Drug Administration (FDA) cleared the H4 coil for use as an aid in short-term smoking cessation for adults (Deep TMS, BrainsWay, Jerusalem, Israel).…”
Section: Extant Literature Of Tms For Substance Use Disorders Smoking...mentioning
confidence: 99%
“…Par ailleurs, ce traite ment n'a pas fait l'objet d'études chez toutes les populations, comme les personnes atteintes de schizophrénie, qui présentent des taux élevés de consommation chronique de tabac. Une étude de validation a montré son potentiel d'utilisation chez la patientèle schizophrène 16 , mais aucun essai de grande envergure visant à déterminer les issues liées à l'abandon du tabagisme n'a été mené pour l'instant. D'autres études devraient évaluer si les protocoles de traite ment combinant la SMTr et les pharmacothérapies antitaba giques peuvent mener à une hausse des taux ou de la longueur des périodes d'abstinence.…”
Section: Que Nous Réserve L'avenir?unclassified
“…Indeed, the LPFC, and especially the dorsolateral PFC (DLPFC) have been implicated in the pathogenesis of several psychiatric and neurologic disorders with affected reward-related behavior, including schizophrenia, anxiety, and posttraumatic stress disorder ( Hopper et al, 2008 ; Maresh et al, 2014 ; Subramaniam et al, 2015 ; Park et al, 2016 ; Pu et al, 2016 ; Zhang et al, 2016 ). Moreover, there is evidence for the efficacy of transcranial magnetic stimulation (TMS) over the PFC for the treatment of other conditions with impaired reward-related behavior such as depression, addictions, Alzheimer’s disease, schizophrenia, and eating disorders ( Fox et al, 2014 ; Moeller et al, 2022 ). These effects are attributed to the technique’s ability to redress imbalances in the excitability of brain networks and neurotransmitter concentrations that characterize these conditions ( Pell et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%